Assessing the Model Risk with Respect to the Interest Rate Term Structure under Solvency II - Martin, Michael (The Journal of Risk Finance, 2013)
Purpose Interest rate risk, i.e. the risk of changes in the interest rate term structure, is of high relevance in insurers' risk management. Due to large capital investments in interest rate sensitive assets such as bonds, interest rate risk plays a considerable role for deriving the solvency capital requirement (SCR) in the context of Solvency II. This paper seeks to address these issues. Design/methodology/approach In addition to the Solvency II standard model, the author applies the model of Gatzert and Martin for introducing a partial internal model for the market risk of bond exposures. After introducing calibration methods for short rate models, the author quantifies interest rate and credit risk for corporate and government bonds and demonstrates that the type of process can have a considerable impact despite comparable underlying input data. Findings The results show that, in general, the SCR for interest rate risk derived from the standard model of Solvency II tends to the SCR achieved by the short rate model from Vasicek, while the application of the Cox, Ingersoll, and Ross model leads to a lower SCR. For low‐rated bonds, the internal models approximate each other and, moreover, show a considerable underestimation of credit risk in the Solvency II model. Originality/value The aim of this paper is to assess model risk with focus on bonds in the market risk module of Solvency II regarding the underlying interest rate process and input parameter

Determinants and Value of Enterprise Risk Management: Empirical Evidence from the Literature - Gatzert, Nadine; Martin, Michael (Risk Management and Insurance Review, 2015)
The development of an enterprise risk management (ERM) program enables companies to manage corporate risks in a holistic manner as opposed to the silo-based perspective in traditional risk management frameworks. One main question in this regard is what factors drive the implementation of an ERM system in companies and whether ERM programs can actually create value once implemented. This article addresses these questions by conducting a comparative assessment of empirical evidence from the literature regarding the determinants of ERM and its value once implemented. In doing so we are able to illustrate differences in model specifications and the underlying data. Our literature study shows that particularly the company size and the level of institutional ownership are significantly positively related to the implementation of ERM in most empirical studies and, furthermore, that ERM generally has a (significant) positive impact on corporate value and performance (to a different extent and depending on the focus of the studies). However, geographic and/or industrial restrictions regarding the underlying data sets partly limit the generalization of the empirical result

Quantifying Credit and Market Risk Under Solvency II: Standard Approach Versus Internal Model - Gatzert, Nadine; Martin, Michael (Insurance Mathematics & Economics, 2012)
Even though insurers predominantly invest in bonds, credit risk associated with government and corporate bonds has long not been a focus in their risk management. After the crisis of several European countries, however, credit risk has recently been paid greater attention. Nevertheless, the latest version of the Solvency II standard model (QIS 5), provided by regulators for deriving solvency capital requirements, still does not require capital for credit risk inherent in, e.g., EEA issued government bonds from Greece or Spain. This paper aims to provide an alternative approach and compares the standard model with a partial internal risk model using a rating-based credit risk model that accounts for credit, equity, and interest rate risk inherent in a portfolio of stocks and bonds. The findings demonstrate that solvency capital requirements strongly depend on the quality and composition of an insurer's asset portfolio and that model risk in regard to model choice and calibration plays an important role in the quantification.
WiSo-Import:2015-03-26:4093
Keywords: Credit Risk; Market Risk; Solvency II; Standard Approach; Internal Model

Valuation and Risk Assessment of Participating Life Insurance in the Presence of Credit Risk - Eckert, Johanna; Gatzert, Nadine; Martin, Michael (Insurance Mathematics & Economics, 2016)